PENGARUH INDUSTRI RUMAHAN KERAJINAN SANGKAR BURUNG TERHADAP PEREKONOMIAN MASYARAKAT SANGGRAAGUNG SOCAH BANGKALAN - Mashudi Mashudi; Misbahul Ali (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2024)
This study was motivated by the researcher's curiosity about the influence of the home industry of bird cage crafts on improving society's economy in the village of Sanggra Agung, which has been doing these crafts for generations. Although they continuously produce bird cages, it seems that the economy of the bird cage craftsmen is still not growing. The study was carried out using a quantitative non-sampling method because the number of craftsmen was still below 100, and the data were obtained from the responses to the craftsmen's questionnaire and observations in the field about the home industry of bird cage crafts. From the results of the validity and reliability instrument tests, as well as the data normality assumption test, no deviations were found in the instrument or questionnaire data. Based on a simple regression analysis, it shows that the variable in the home industry of bird cage crafts affects the community economy, although the effect is not very significant. The coefficient correlation value is 0.211 or 4.5%, and the remaining 95.5% is influenced by other variables not discussed in this study.